Steroids in cardiac surgery: a systematic review and meta-analysis. (April 2018) - Dvirnik, N.; Belley-Cote, E.P.; Hanif, H.; Devereaux, P.J.; Lamy, A.; Dieleman, J.M.; Vincent, J.; Whitlock, R.P.
Abstract: Background: Cardiopulmonary bypass (CPB) induces a systemic inflammatory reaction that may contribute to postoperative complications. Preventing this reaction with steroids may improve outcomes. We performed a systematic review to evaluate the impact of prophylactic steroids on clinical outcomes in patients undergoing on-pump cardiac surgery. Methods: We searched MEDLINE, EMBASE, and Cochrane CENTRAL for randomised controlled trials (RCTs) comparing perioperative corticosteroid administration with a control group in adults undergoing CPB. Outcomes of interest included mortality, myocardial infarction, and new onset atrial fibrillation. We assessed the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation approach. Results: Fifty-six RCTs published between 1977 and 2015 were included in this meta-analysis. Mortality was not significantly different between groups [3.0% (215/7258 patients) in the steroid group and 3.5% (252/7202 patients) in the placebo group; relative risk (RR), 0.85; 95% confidence interval (CI), 0.71–1.01; P =0.07; I 2  = 0%]. Myocardial injury was more frequent in the steroid group [8.0% (560/6989 patients), compared with 6.9% (476/6929 patients); RR, 1.17, 95% CI, 1.04–1.31; P =0.008; I 2 =0%]. New onset atrial fibrillation was lower in the steroid group [25.7% (1792/6984 patients) compared with 28.3% (1969/6964 patients), RR, 0.91, 95% CI, 0.86–0.96, P =0.0005, I 2 =43%]; this beneficial effect was limited to small trials ( P for interaction <0.00001). Conclusions: After randomising 16 013 patients, steroid administration at the time of cardiac surgery had an unclear impact on mortality, increased the risk of myocardial injury, and the impact on atrial fibrillation should be viewed with caution given that large trials showed no effect.